A new species of Indonemoura fujianensis complex (Plecoptera: Nemouridae) from Central China, with female association of I. auriformis Li & Yang, 2008 - Li, Wenliang; Yang, Ding; Li, Weihai (Zootaxa, 2020)
A new species of the Indonemoura fujianensis complex of in the genus Indonemoura Baumann 1975 (Plecoptera: Nemouridae), I. wangae sp. nov. is described from the Shennongjia National Natural Reserve, Hubei Province of Central China. This new taxon is compared with other related members of the I. fujianensis complex. The female of I. auriformis Li & Yang, 2008 is positively associated based on mating pairs recently collected. In the original description, the female of this was erroneously associated and is considered now as an unidentified Indonemoura female herein.